The Basic Structure of Qur’anic Worldview: An Analysis to Toshihiko Izutsu Concept of Weltanschauung - Muhammad Badrun; Alhafidh Nasution; Azizatul Afini; Evi Nurdiana (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This article discusses the concept of the Quranic worldview in the view of Toshihiko Izutsu. This is important to study because the Qur'an is the holy book of Muslims that significantly influences human life. This Japanese scholar also describes how the relationship between God and man uses semantic analysis. He explained that the relationship between God and man has four parts: ontology, god and servant, ethics, and communication. Izutsu also asserts that communicating with God through the Qur'an is not only read and is a theory but also involves practice. This study uses qualitative methods with a type of literature analysis supplemented by analysis of content to analyze the izutsu concept of worldview, distinguished by systematic method, to accomplish this purpose. As a result, according to him, the Qur'anic worldview separates his beliefs into six categories: namely, the ideas of God and man, the Muslim community, the idea of the visible and invisible, the idea of the Day of Judgment, and the idea of eschatological.